Cultural Values in the Film Barakati - Annisa Mutmainah; Dedi Warsana (Cinematology: Journal Anthology of Film and Television Studies, 2021)
The film “Barakati” is a historical and adventure genre film that combines cultural elements from Buton Island and Yogyakarta. This film tells the story of an expedition involving a young archaeologist, a foreign journalist, a woman from Buton, and also someone who is a descendant of the Majapahit Kingdom. The method used in this study is a qualitative research method. Qualitative research methods are descriptive and analytical methods. In this study, a description of the results of observing the plot of this film was carried out which was then analyzed against the cultural values contained in the film "Barakati". The analysis is in the form of a culture that seems to be still thick with the region, whether it is in the culture on the island of Buton or in Yogyakarta. In this study, the analysis used to describe cultural values in the film "Barakati" is Charles Sanders Peirce's Semiotic Analysis. Charles Sanders Peirce divides signs into 3, namely: icons, indexes and symbols. The results obtained in this study show the cultural values contained in this film. These cultural values are historical objects whose existence is still maintained today. The existence of these historical objects has the meaning and characteristics of each depending on its function. Cultural values related to these historic objects must also be preserved because they are cultural assets as a marker or cultural identity of a nation.